Advertisement Remove all ads

Solve the Following Equation: X +3 3x- 7 --=-x+ 2 2x- 3 - Mathematics

Sum

Solve the following equation:  `("x" + 3)/("x" + 2) = (3"x" - 7)/(2"x" - 3)` 

Advertisement Remove all ads

Solution

`("x" + 3)/("x" + 2) = (3"x" - 7)/(2"x" - 3)` 

(x + 3)(2x - 3) = (3x - 7)(x + 2) 

2x2 + 6x - 3x - 9 = 3x2 - 7x + 6x - 14 

2x2 + 3x - 9 = 3x2 - x - 14 

(3 - 2)x2 +(-1 - 3) x + (- 14 + 9) = 0 

x2 - 4x -5= 0

x2 + x - 5x - 5 = 0

x (x+ 1) - 5 (x + 1) = 0 

( x + 1)(x - 5) = 0

(x+ 1)= 0, (x - 5)= 0

X = -1 , x = 5

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Frank ICSE Class 10 Mathematics Part 2
Chapter 6 Quadratic Equations
Exercise 6.1 | Q 20
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×